Management of difficult-to-treat patients with ulcerative colitis: focus on adalimumab - Armuzzi A; Pugliese D; Nardone OM; Guidi L (Dove Medical Press, 2013)
Alessandro Armuzzi, Daniela Pugliese, Olga Maria Nardone, Luisa Guidi IBD Unit, Complesso Integrato Columbus, Catholic University, Rome, Italy Abstract: The treatment of ulcerative colitis has changed over the last decade, with the introduction of biological drugs. This article reviews the currently available therapies for ulcerative colitis and the specific use of these therapies in the management of patients in different settings, particularly the difficult-to-treat patients. The focus of this review is on adalimumab, which has recently obtained approval by the European Medicines Agency and the US Food and Drug Administration, for use in treating adult patients with moderate-to-severe, active ulcerative colitis, who are refractory, intolerant, or who have contraindications to conventional therapy, including corticosteroids and thiopurines. Since the results emerging from the pivotal trials have been subject to some debate, the aim of this review was to summarize all available data on the use of adalimumab in ulcerative colitis, focusing also on a retrospective series of real-life experiences. Taken together, the current evidence indicates that adalimumab is effective for the treatment of patients with different types of ulcerative colitis, including biologically naïve and difficult-to-treat patients. Keywords: randomized controlled trials, real-life experiences